Discharge Body Mass Index, Not Illness Chronicity, Predicts 6-Month Weight Outcome in Patients Hospitalized With Anorexia Nervosa - Redgrave, Graham W.; Schreyer, Colleen C.; Coughlin, Janelle W.; Fischer, Laura K.; Pletch, Allisyn; Guarda, Angela S. (Frontiers in Psychiatry, 2021)
Proposed treatments for severe and enduring anorexia nervosa (SE-AN) focus on quality of life, and psychological and social functioning. By de-emphasizing weight restoration as a priority, however, premature diagnosis of SE-AN may reduce potential for recovery. The present study assessed the effect of weight restoration, illness duration, and severity on treatment outcome six months after discharge from an intensive, meal-based behavioral treatment program. Participants included hospitalized adult women (N=191) with AN or underweight other specified feeding and eating disorder (OSFED). Participants were characterized as short-term (ill<7 yrs; n=74) or long-term ill (ill≥7 yrs; n=117). Compared with short-term ill, long-term ill patients were older, had lower lifetime body mass index (BMI), more prior admissions, and exhibited higher depression and neuroticism. Long-term vs. short-term ill patients gained weight at the same rate (~2 kg/wk) and were equally likely to be weight restored by discharge (>75% reached BMI ≥ 19 kg/m2 in both groups). At 6-month follow-up (n=99), both groups had equivalent self-reported BMI, and depression, drive for thinness, body dissatisfaction, and bulimia scores. The only predictor of BMI ≥ 19 kg/m2 at follow-up was discharge BMI. The likelihood of a BMI ≥ 19 kg/m2 at follow-up was fivefold higher for those with discharge BMI ≥ 19 kg/m2. Few studies of long-term ill inpatients with AN have examined the impact of full weight restoration on short-term outcomes. This study supports the therapeutically optimistic stance that, regardless of illness duration, hospitalized patients with AN benefit from gaining weight to a BMI ≥ 19 kg/m2.